Towards Community Sensing - Horvitz, Eric; Kansal, Aman; Zhao, Feng (International Conference on Information Processing in Sensor Networks (IPSN), 2008)
A great opportunity exists to fuse information from pop- ulations of privately-held sensors to create useful sensing applications. For example, GPS devices, embedded in cell- phones and automobiles, might one day be employed as distributed networks of velocity sensors for traffic monitor- ing and routing. Unfortunately, privacy and resource con- siderations limit access to such data streams. We describe principles of community sensing that offer mechanisms for sharing data from privately held sensors. The methods take into account the likely availability of sensors, the context- sensitive value of sensor information, based on models of phenomena and demand, and sensor owners’ preferences about privacy and resource usage. We present efficient and well-characterized approximations of optimal sensing poli- cies. We provide details on key principles of community sensing and highlight their use within a case study for road traffic monitoring.